2008
DOI: 10.4161/cc.7.4.5442
|View full text |Cite
|
Sign up to set email alerts
|

Integration of energy metabolism and the mammalian clock

Abstract: Circadian clocks synchronize diverse biological processes in organism to 24-hour light-dark cycles. The rhythmic activation of selective pathways enables the organisms to optimize their ability to store and generate chemical energy, to minimize environmental stresses, and to reproduce through cell growth and division cycles. In mammalian tissues, major metabolic pathways exhibit robust diurnal rhythms, including glucose and lipid metabolism as well as mitochondrial fuel oxidation. This temporal organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 79 publications
0
39
0
Order By: Relevance
“…These regulatory elements included FXR, the hormone adiponectin (AdipoQ), the nuclear retinoid X receptors RXRα and RXRβ, and the PPARs. PPARα is known to be regulated diurnally and interacts with regulators of circadian rhythm (Clock/Bmal1) (31). We observed that gastrointestinal BSH1 activity also promotes a significant shift in the expression pattern of genes normally regulated by circadian rhythm.…”
Section: Discussionmentioning
confidence: 81%
“…These regulatory elements included FXR, the hormone adiponectin (AdipoQ), the nuclear retinoid X receptors RXRα and RXRβ, and the PPARs. PPARα is known to be regulated diurnally and interacts with regulators of circadian rhythm (Clock/Bmal1) (31). We observed that gastrointestinal BSH1 activity also promotes a significant shift in the expression pattern of genes normally regulated by circadian rhythm.…”
Section: Discussionmentioning
confidence: 81%
“…The intrinsic nature of its highly specialized, temporally regulated transcription places the cellular clock as a prominent model for the study of dynamic chromatin remodeling. 38,39 Moreover, based on the tight coupling between circadian rhythms and metabolic regulation, 18 clock-controlled chromatin reorganization is likely to reveal specific pathways linking histone modifications to cellular metabolism. For example, the central clock protein Clock has histone acetyltransferase (HAT) enzymatic properties.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the ROR and Rev-erb families of orphan nuclear receptors couple metabolic functions to the clock oscillators by orchestrating these two systems simultaneously. 18 Other nuclear factors, including peroxisome proliferator-activated receptors (PPARs) and glucocorticoid receptor (GR), can serve as output regulators of the clock oscillators. 18 Second, metabolites can act as the integrators of clock and metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The master clock in mammals is located in the suprachiasmatic nucleus (SCN) of the hypothalamus, and many physiological processes are subject to circadian oscillations, including lipid and carbohydrate metabolism, hormone secretion, and feeding behaviors (Eckel-Mahan and Sassone-Corsi 2013; Liu et al 2013;Adamovich et al 2014). In the liver, the circadian clock is closely related to the rhythmicity of hepatic metabolism (Lin et al 2008;Tahara and Shibata 2016). The autonomous rhythm of hepatocytes is entrained by not only the hormonal and neuronal signals from the master clock but also the nutrients and metabolites whose oscillation is in large part determined by feeding activity (Kornmann et al 2007;Feng and Lazar 2012).…”
mentioning
confidence: 99%